It's a long road to a tomato : tales of an organic farmer who quit the big city for the (not so) simple life - Stewart, Keith, 1944- (Experiment, 2010)
Presents essays on the author's midlife development as a farmer, with tips on organic vegetable growing and selling in an urban market, and insights into the issues surrounding agriculture.